The Relationship Between Pregnancy Exercises And The Labor Process Of Mothers In Labor At The Nur Kholidah Pulungan Clinic - Meirani, Putri (Cattleya Darmaya Fortuna, 2024)
Maternal and perinatal mortality rates in Indonesia are still quite high, one of the causes of high mortality is due to prolonged labor. Pregnancy exercise is an exercise program to prepare the mother's physical condition by maintaining the condition of the muscles and joints that play a role in the labor process, as well as an important method to maintain or improve the physical balance of pregnant women and is an exercise therapy given to pregnant women with the aim of achieving a fast, easy and safe delivery and preventing the occurrence of stage II. This study design is cross-sectional with secondary data collection. The population in this study was 25 and sampling was carried out using the total sampling technique. Data analysis used Chi Square. The results of the study of 25 respondents who participated in pregnancy exercise as many as 21 people (84%) participated in pregnancy exercise and 4 respondents (16%) did not participate in pregnancy exercise. The results of the statistical test with the